MicroRNAs as regulators of mitochondrial function: Role in cancer suppression - Tomasetti, Marco; Neuzil, Jiri; Dong, Lanfeng (Biochimica et biophysica acta, 2014)
Mitochondria, essential to the cell homeostasis maintenance, are central to the intrinsic apoptotic pathway and their dysfunction is associated with multiple diseases. Recent research documents that microRNAs (miRNAs) regulate important signalling pathways in mitochondria, and many of these miRNAs are deregulated in various diseases including cancers. In this review, we summarise the role of miRNAs in the regulation of the mitochondrial bioenergetics/function, and discuss the role of miRNAs modulating the various metabolic pathways resulting in tumour suppression and their possible therapeutic applications. MiRNAs have recently emerged as key regulators of metabolism and can affect mitochondria by modulating mitochondrial proteins coded by nuclear genes. They were also found in mitochondria. Reprogramming of the energy metabolism has been postulated as a major feature of cancer. Modulation of miRNAs levels may provide a new therapeutic approach for the treatment of mitochondria-related pathologies, including neoplastic diseases. The elucidation of the role of miRNAs in the regulation of mitochondrial activity/bioenergetics will deepen our understanding of the molecular aspects of various aspects of cell biology associated with the genesis and progression of neoplastic diseases. Eventually, this knowledge may promote the development of innovative pharmacological interventions. This article is part of a Special Issue entitled Frontiers of Mitochondrial Research. •MiRNAs have been found in mitochondria and regulate mitochondrial activity/function.•MiRNAs are deregulated in various diseases including cancers.•Reprogramming of the metabolism has been postulated as a major feature of cancer.•MiRNAs modulate various metabolic pathways resulting in tumour suppression.•Modulation of miRNAs levels provides a new therapeutic approach for cancer treatment.